The role of technical and vocational education and training institutions in the Namibian National System of Innovation : a case study of community skills development centres in the hospitality and tourism sectors - Katire, Ferdinand (Stellenbosch : Stellenbosch University, 2024)

(untitled)
Thesis (MPA)--Stellenbosch University, 2024.